PARENTS' BEHAVIOR IN GIVING DRUG IN CHILDREN WITH TUBERCULOSIS IN POLYCLINIC CHILDREN RSUD. DR. PIRNGADI MEDAN - Ariga, Reni Asmara; Amelia, Rina (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Lung tuberculosis (TB) is one of the diseases that need special attention in Indonesia; this is because Indonesia is ranked third after the world of India and China with patients about 10% of the total number of TB patients in the world. This research aims to identify the picture of behavior parents in the provision of drugs in children with TB in Children Polyclinic RSUD. Dr. Pirngadi Medan. This study uses descriptive design with the number of samples of 42 respondents. Samples were taken using consecutive sampling technique. The data were collected using a knowledge, attitude, and action questionnaire. The data collected were analyzed using descriptive statistics, then the result of data analysis is presented in frequency distribution table and percentage. The result of this research indicates that the majority of respondents have good knowledge as much as 85.7%, and the majority of respondents have good attitude of 76.2% while the majority of respondents have an adequate action of 52.3%. The results of this study can be used as information and reference for child and community nurses in providing nursing care, especially health education and monitoring of treatment for patients with pulmonary TB in undergoing treatment.